LEAF MORPHOLOGY AND ANATOMY OF VARIETIES OF TURNERA DIFFUSA VAR. DIFFUSA AND TURNERA DIFFUSA VAR. APHRODISIACA (WARD) URB - Baez-Parra, Karla Marina; Alcaraz-Melendez, Lilia; Santamaria-Miranda, Apolinar; Heredia, Jose Basilio; Leon-Felix, Josefina; Muy-Rangel, Maria Dolores; Angulo-Escalante, Miguel Angel (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Mexican damiana (Turnera diffusa Willd. Ex. Schult), specifically damiana of California has a high demand in the international market for its popularity as aphrodisiac, but its marketing has been affected by the adulteration of its products due to a lack of authentication mechanisms and limited information on the differences between the two currently known varieties. The aim of this study was to establish a leaf standard monograph with scientific bases of the varieties aphrodisiaca and diffusa of Turnera diffusa Willd. Ex. Schult, cultivated at the same agronomic and environmental conditions. Material and Methods: Damiana leaves were collected from a cultivar located in the municipality of Culiacan, Sinaloa, Mexico in 2016. The pharmacognostic studies were carried out in terms of macroscopic and both optical and electronic microscopic characteristics of leaves of the two varieties for their distinction. Results: The leaves of diffusa variety were twice as large as those of the aphrodisiaca variety, whereas papillose glandular trichomes were observed with greater density in the aphrodisiaca variety than those on diffusa leaves where unicellular trichomes were the ones observed in greater density. The leaves of both varieties are dorsiventral and hypostomatic with paracytic stomata. Conclusion: The obtained qualitative and quantitative leaf standards provide reference information for the proper identification and monograph preparation of the aphrodisiaca and diffusa varieties of Turnera diffusa. Pharmacognostic characteristics such as the type of stomata, trichomes, and leaf identify the species, whereas characteristics as leaf size and trichome density differ between varieties.